Marks of difference: notes on indigenous presence in Cuba - Ciccarone, Celeste (Geografares, 2023)
Between a field diary, textual research and ethnographic methods, this research report, carried out in Cuba in the second half of 2019, is an offshoot of a research project entitled Marks of Difference: notes for an ethnography of afro-indigenous relationships in Cuba and Brazil. The aim of this project was to conduct a comparative study of concrete assemblages of African and Amerindian collectives in Cuba and Brazil as counter-narratives to nationalist theories of miscegenation and syncretism.
Keywords: racial mixture; nacionalism; marks of difference